2013
DOI: 10.1021/cb400030n
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Effect of the Ribosomal Surface on Nascent Polypeptide Dynamics

Abstract: The crucial molecular events accompanying protein folding in the cell are still largely unexplored. As nascent polypeptides emerge from the ribosomal exit tunnel, they come in close proximity with the highly negatively charged ribosomal surface. How is the nascent polypeptide influenced by the ribosomal surface? We address this question via the intrinsically disordered protein PIR and a number of its variably charged mutants. Two different populations are identified: one is highly spatially biased, and the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
117
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(127 citation statements)
references
References 56 publications
10
117
0
Order By: Relevance
“…Fluorescence spectroscopy of ribosome-bound nascent chains (RNCs) has recently been used to increase our understanding of aspects of protein biogenesis, such as protein trafficking (Flanagan et al 2003;Woolhead et al 2004;Holtkamp et al 2012), chaperone recognition (Lin et al 2012), and cotranslational protein folding (Ellis et al 2008;Knight et al 2013). Unfortunately, the presence of the ribosome hampers standard labeling of RNCs, necessitating the use of alternative strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence spectroscopy of ribosome-bound nascent chains (RNCs) has recently been used to increase our understanding of aspects of protein biogenesis, such as protein trafficking (Flanagan et al 2003;Woolhead et al 2004;Holtkamp et al 2012), chaperone recognition (Lin et al 2012), and cotranslational protein folding (Ellis et al 2008;Knight et al 2013). Unfortunately, the presence of the ribosome hampers standard labeling of RNCs, necessitating the use of alternative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the former, site-specific incorporation of a single fluorophore is largely restricted to rare proteins with a single lysine (Lin et al 2012), because lysine residues are highly abundant in proteins. The use of tRNA fMet is also limited, as it allows only N-terminal protein labeling (Ellis et al 2008;Knight et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…[1] They play an important role in the binding of proteins to small ligands, [2] proteins, [3] DNA, [4] and other molecules. [5] It has also been shown that protein thermostability can be improved through optimizing the surface charge-charge interactions. [6] As two ionizable residues with opposite charges approach to each other,as alt bridge is formed.…”
mentioning
confidence: 99%
“…As the exterior of the ribosome consists for a large part of rRNA, it is negatively charged in many areas. Negative charge also surrounds the exit tunnel, thereby providing an environment that is very different from the cytoplasm (177). This charge may influence protein folding, as it attracts positively charged residues of the nascent chain and repels negatively charged ones (170).…”
Section: Protein Folding In Vivomentioning
confidence: 99%
“…This charge may influence protein folding, as it attracts positively charged residues of the nascent chain and repels negatively charged ones (170). It also restricts the dynamics of nascent chains according to their charge (177). Due to these electrostatic interactions, nascent chains may be protected from misfolding or aggregation.…”
Section: Protein Folding In Vivomentioning
confidence: 99%